Green Synthesis of Cadmium Nanoparticles Using Laurus nobilis for Dye Degradation: Sintesis Hijau Nanopartikel Kadmium Menggunakan Laurus nobilis untuk Degradasi Pewarna - Rusul Sami Jabber; Zainab TYAl-Abdullah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Nanotechnology has gained significant attention for its potential applications in environmental remediation, particularly in the degradation of organic pollutants. Specific Background: Green synthesis of nanoparticles using plant extracts is a sustainable approach that reduces the need for hazardous chemicals. Knowledge Gap: However, the role of Laurus nobilis (bay laurel) in synthesizing cadmium nanoparticles (CdNPs) and their effectiveness in dye degradation remains underexplored. Aims: This study investigates the feasibility of synthesizing CdNPs using Laurus nobilis leaf extract as a natural reducing and stabilizing agent and evaluates their potential in methylene blue (MB) dye degradation. Results: The formation of CdNPs was confirmed by UV-visible spectroscopy, exhibiting a surface plasmon resonance peak at 435 nm, and SEM-EDX analysis revealed spherical nanoparticles with an average size of 61.36 nm and a cadmium composition of 87.57%. The synthesized CdNPs achieved a 60% degradation efficiency for MB dye under visible light exposure. Novelty: This work presents an eco-friendly, rapid, and simple method for synthesizing CdNPs using Laurus nobilis, highlighting the phytochemical-mediated nanoparticle stabilization. Implications: The findings demonstrate the potential of plant-based CdNPs for wastewater treatment applications, contributing to sustainable and green chemistry solutions for environmental pollution. Highlights: Green synthesis of cadmium nanoparticles using Laurus nobilis extract. Spherical CdNPs (61.36 nm) achieved 60% methylene blue degradation. Eco-friendly nanotechnology for wastewater treatment and environmental remediation. Keywords: cadmium nanoparticles, degradation, green synthesis, Laurus nobilis Leaves extract.